Toxicity, pollution and biodegradation of acrylamide – a mini review (Journal of Biochemistry, Microbiology and Biotechnology, 2015)
Acrylamide is a monomer to polyacrylamide; a polymer with diverse application in basic research, industries and agriculture. The monomer is highly toxic while the polymeric form is slowly degraded to its monomeric form in the environment. In this mini review, the toxicity, uses, pollution and biodegradation of this important monomer are discussed. An important aspect of this review is to highlight the application of microorganisms as remediating agent for the removal of this compound from the environment.
Keywords: acrylamide; polyacrylamide; toxicity; biodegradation; bioremediation